(untitled) (Economic and Political Thought, 2010)
The article discusses Turkish – Russian relations in the context of changes that have been taking place in the international system since World War II. In the first years after the war they were hostile as a result of the cold war confrontation. After the fall of the Iron Curtain, together with the changing geopolitics in the Euro-Asiatic region, Turkish and Russian interests started to more and more coincide in many fields of international policy. Today, although there are still controversial issues between Ankara and Moscow, their relations, especially in the area of economy, are kept at a very high level.